Analisis Kinerja Keuangan dan Risiko Pembiayaan dalam Penerapan Prinsip Syariah pada Bank Syariah - Yunni, Yunni; Harahap, Rahmat Daim; Anggraini, Tuti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The rapid growth of the Islamic banking industry in Indonesia has not been matched by institutional strengthening at the micro level, particularly within Islamic Rural Banks (BPRS). This study aims to analyze the financial performance and financing risk of PT. BPRS Puduarta Insani from 2021 to 2024, and to evaluate the implementation of Sharia principles in operational practices from the perspective of Account Officers (AOs). Employing a qualitative approach, the research utilizes in-depth interviews supported by secondary financial data and applies thematic analysis. The findings reveal a significant phenomenon of pseudo-compliance, where Sharia principles are fulfilled formally but not substantively. This practice, driven by institutional pressure to achieve financing targets, directly contributes to a deteriorating portfolio quality and distortion in the application of Sharia contracts. The issue is further exacerbated by limitations in AO capacity, a weak monitoring system, and the lack of standardized recovery procedures, compounding risk management challenges. This study recommends institutional reform through the rationalization of financing targets, enhancement of operational Sharia training, and digitalization of monitoring systems to ensure a sustainable balance between financial performance and Sharia integrity.